A 23-Year Bibliometric Study of the Journal of Food Products Marketing. Issue 5 (3rd July 2016) - Dabirian, Amir; Diba, Hoda; Tareh, Farzaneh; Treen, Emily
ABSTRACT: This article presents a statistical review of the Journal of Food Products Marketing publication for the past 23 years, from the journal's inception in 1992 through to 2014. The intent of this article is to highlight the publication's contribution to discourse within the global food industry. A total of 505 papers were analyzed through bibliometric techniques to identify the journal's most significant findings and trends. An appropriate introduction of the journal's nature and scope in the industry allowed for further analysis of research articles within the journal. From this analysis, five major themes emerged for further study, which include content, manuscript, citations and reference, authorship, and special editions.